NCMP-19. STROKE IN CANCER PATIENTS. (11th November 2019) - Ching, Marilou; Komlodi-Pasztor, Edina
Abstract: Patients with malignancy have an increased tendency for venous and arterial embolism, and for increased risk for bleeding. Clinical decisions regarding anticoagulation in this population has been challenging and complicated by the availability of various anticoagulants. Currently, there is no evidence-based guideline available for the prevention of arterial embolism and thrombosis, such as stroke, in cancer patients. The aim of the study is to assess the use of anticoagulant medications in cancer patients who suffer a stroke. ICD-9/-10 codes were used to identify patients with cancer who were admitted between September 1, 2017 and November 30, 2017 to the Buffalo General Hospital with the diagnosis of stroke. Chart review was used to verify the history of cancer and stroke and to collect additional information. The diagnosis of acute stroke and cancer were verified in 87 patients. Among them, 31 patients had active malignancy. Of the 31 patients, 9 were diagnosed with intracranial hemorrhage and 22 with ischemic strokes. Of the 9 patients with intracranial hemorrhage, 3 were anticoagulated and 1 patient was off anticoagulation. Of the 22 patients with ischemic stroke, 4 patients were anticoagulated, although 1 patient was underdosed based on INR. Seven of the 22 patients were taken off of anticoagulation; 3 had side effects and 4 were awaiting a surgical procedure. Five of the 9 patients with intracranial hemorrhage and 10 of the 22 patients with ischemic stroke were made comfort care and passed away shortly after the diagnosis of stroke.